Y-aromaticity – existing: yes or no? An answer given on the magnetic criterion (TSNMRS) - Kleinpeter, Erich; Koch, Andreas (Tetrahedron, 2016)
The spatial magnetic properties (Through Space NMR Shieldings – TSNMRS) of a number of Y-shaped structures possessing 4n+2 π-electrons (i.a. the trimethylenemethane ions TMM2+, TMM2−, the guanidinium cation, substituted and hetero analogues) have been computed, visualized as Isochemical Shielding Surfaces (ICSS) of various size and direction, were examined subject to present Y-aromaticity and the results compared with energetic and geometric criteria obtained already. [Display omitted]